Microwaves can kill malaria parasites non-thermally - Coronado, Lorena M.; Stoute, José A.; Nadovich, Christopher T.; Cheng, Jiping; Correa, Ricardo; Chaw, Kevin; González, Guadalupe; Zambrano, Maytee; Gittens, Rolando A.; Agrawal, Dinesh K.; Jemison, William D.; Donado Morcillo, Carlos A.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Malaria, which infected more than 240 million people and killed around six hundred thousand only in 2021, has reclaimed territory after the SARS-CoV-2 pandemic. Together with parasite resistance and a not-yet-optimal vaccine, the need for new approaches has become critical. While earlier, limited, studies have suggested that malaria parasites are affected by electromagnetic energy, the outcomes of this affectation vary and there has not been a study that looks into the mechanism of action behind these responses. In this study, through development and implementation of custom applicators for in vitro experimentation, conditions were generated in which microwave energy (MW) killed more than 90% of the parasites, not by a thermal effect but via a MW energy-induced programmed cell death that does not seem to affect mammalian cell lines. Transmission electron microscopy points to the involvement of the haemozoin-containing food vacuole, which becomes destroyed; while several other experimental approaches demonstrate the involvement of calcium signaling pathways in the resulting effects of exposure to MW. Furthermore, parasites were protected from the effects of MW by calcium channel blockers calmodulin and phosphoinositol. The findings presented here offer a molecular insight into the elusive interactions of oscillating electromagnetic fields with P. falciparum, prove that they are not related to temperature, and present an alternative technology to combat this devastating disease.